Dear Reader! - Lukács, János (Public Finance Quarterly, 2025)
Thank you for your continued interest in the Financial Review and for once again taking the time to read the exciting and informative articles in this issue. As you know, our journal focuses on public finance, with articles on the functioning of the public sector and the national economy, financial and economic policy systems, monetary and fiscal policy analysis, financial innovation, derivatives, corporate and national financial accounting techniques, financial investments, return and risk calculations for various securities, loans and the dissemination of financial literacy. This issue also examines the development of the financial sector in a macroeconomic framework and its social and economic psychology.